New 12kW three-phase 18-pulse high power factor AC-DC converter with regulated output voltage for rectifier units - de Seixas, Falcondes Jose Mendes [UNESP] (1999)
This work presents a new high power factor three-phase rectifier based on a Y-connected differential autotransformer with reduced kVA and 18-pulse input current followed by three DC-DC boost converters. The topology provides a regulated output voltage and natural three-phase input power factor correction. The lowest input current harmonic components are the 17th and the 19th. Three boost converters, with constant input currents and regulated parallel connected output voltages are used to process 4kW each one. Analytical results from Fourier analyses of winding currents and the vector diagram of winding voltages are presented. Simulation results to verify the proposed concept and experimental results are shown in the paper.